Effects of innovation on employment: An analysis at the firm level in Bolivia - Carlos Foronda; Javier Beverinotti (Inter-American Development Bank (IDB), 2021)
This study quantifies the impact of process and product innovation on employment growth in Bolivia by using microdata from a survey on innovation conducted in Bolivia in 2016. Following the model of Harrison, Jaumandreu, Mairesse, and Peters (2008) and the adaptations for Latin America of Crespi and Tacsir (2013) and Elejalde, Giuliodori, and Stucchi (2015), we demonstrate that employment growth is explained by product innovation. On the other hand, we find no evidence of a displacement effect due to process innovation. With respect to innovation and work composition, we observe that the reation of qualified employment is slightly favored over that of unqualified employment.
Keywords: D2; O12; O14; O31; O33; O40; 330; employment; product innovation; process innovation; productivity